Tadarus Al-Qur'an in the Month of Ramadhan as a Social-Religious Practice: A Sociological Review and Maqashid Syari'ah in Aceh Besar - Ahmad Tahrir; Avicenna Al Maududdy (Islamic Studies and Civilization Journal, 2026)
This study aims to analyze the practice of Al-Quran recitation during the month of Ramadhan in Aceh Besar as a socio-religious phenomenon through a review of the sociology of Islamic law and the maqashid syari’ah. Using a qualitative approach with descriptive-analytical methods, this study explores how this tradition operates in society. The research findings indicate that: (1) sociologically, tadarus Al-Qur’an in Aceh Besar is a structured social practice that strengthens communal identity and solidarity among residents through interactions in the meunasah or mosque. (2) From the perspective of the sociology of Islamic law, tadarus is a form of living law that functions as an informal social control mechanism in shaping the religious character of society. (3) A review of the maqashid syari’ah proves that tadarus fulfills the five main elements of welfare (al-daruriyyat al-khamsah), especially in maintaining religion (hifdz al-din) and the soul (hifdz al-nafs). This study also reveals the dialectic of loudspeaker use that requires a moderate approach to balance between religious propagation and protection of the right to public tranquility.